The effect of putrescine and difluoromethylornithine on cell division activity of wheat in different ploidy level - (:unkn) unknown (FIRENZE UNIV PRESS, 2005)
Effects of exogenous putrescine (Put) and difluoromethylornithine (DFMO) on seed germination, root growth, mitotic activity and mitotic chromosome behavior were investigated in Triticum monococcum (2x), Triticum durum (4x) and Triticum aestivum (6x). Put and DFMO affected all three species, but diploid species was the most affected one in respect to seed germination, mitotic index and the occurrence of abnormality than the others. Reduction of the root growth in Put and DFMO treated samples was due to the reduction of mitotic activity in three species used in this research.
Keywords: cell division; mitotic activity; ploidy level; polyamines; POLYAMINES; SPERMIDINE; GROWTH; GENOME